AMBITION OF COLONEL CLAUS VON STAUFFENBERG IN VALKYRIE MOVIE (2008) DIRECTED BY BRYAN SINGER : A PSYCHOANALYTIC APPROACH - DAYADI, AGUNG (2011)
The object of the research is the movie entitled Valkyrie movie (2008) directed by Bryan Singer. The study gives focus on psychoanalytic approach as reflected in Bryan Singer's Valkyrie. The aim of the study is finding the criticism on moral and social value. The study belongs to a qualitative study. In this method, the researcher uses two data sources namely primary and secondary data. The primary data source and object of study is the movie Valkyrie itself, meanwhile the secondary is any literature related with the study. The technique of data analysis in this study is descriptive to make an interpretation of the text and content analysis using deductive and inductive method. The result of the study shows the following conclusion. An ambition of life influences the major character Colonel Claus Von Stauffenberg's personality development in avoiding pain and finding pleasure. All His efforts are done to cheer up himself and his friends in order to carry on his life and try to clear an ambition in his life. Even though he has to cope with his own life, he can manage to take care of his friends. He is strong man. He must strive for success and superiority. He has gone through a lot of problems, but he can survive his difficulties. His ego arises from a sense of imperfection mental that motivating him to be better.